Joint use of developed collagen-containing complexes and cell cultures in creating new tissue equivalents - K. V. Kulakova; D. Ya. Aleynik; I. N. Charykova (Бюллетень сибирской медицины, 2017)
The purpose of the study is to assess the possibility of applying the integrated module as the basis of a celltissue equivalent for treatment of wounds of skin and soft tissues. In the frame of the set task the following problems were being solved: research of the spatial structure and architectonics of the surface of the developed base collagen-containing materials and their biocompatibility with cell cultures.Materials and methods. The study of a material which is a two-layer complex film, consisting of collagen and polysaccharide components was carried out. The collagen was separated from the dermis and was then impregnated with particulate demineralized bone matrix (DCM) according to the original methodology. For the purposes of the study the dehydrated material was created in the form of a film. Electron microscopic examination of surfaces was performed on scanning electron microscope JEOL JSM-IT300LV in high vacuum and at low values of probe current (< 0,1 nА). Studies to assess the viability of the cells cultivated on films of collagen material (tested for cytotoxicity and the adhesive capacity) were performed in vitro using strains of diploid human fibroblasts 4–6 passage. The culture condition was visually assessed using an inverted Leica microscope DM IL (Carl Zeiss, Austria), equipped with a computerizes program of control of culture growth (Leica IM 1000).Results. The data obtained in the study of the surface structure of the developed complex module showed that it seems to be promising as a basic component of the cellular-tissue system with its large number of structural formations for fixation of the cells and a well-organized barrier layer capable of vapor - permeability. Experiments in vitro confirmed the absence of toxicity of the material being studied in relation to the culture of dermal human fibroblasts, suggesting the possibility of creation on its basis of cell-tissue complex and further experimental studies in vivo.Conclusion. Thus it was experimentally confirmed that the physical characteristics of the developed integrated module satisfy the requirements for the materials for cultivation of cells. The absence of cytotoxicity on the model of a culture of dermal human fibroblasts allows to make a conclusion about a possibility of its use as the basis of cell-tissue equivalent. Preliminary results indicate the advisability of further experiments in vivo aimed at improving complex collagen-containing materials, the development of different ways of their application and clinical evaluation of the effectiveness in the treatment of wounds of various genesis.